Diabetes mellitus type 1 in congenital rubella syndrome: a case report - Carina Lisa Madarina Julia E.S. Herini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Corina Lisa, Madarina Julia, E.S. Herini . Diabetes Mellitus Type 7 in Congenital Rubella SyndromeDiabetes mellitus type 1 has been reported as a very rare delayed manifestation of congenital rubella syndrome. We reported a confirmed case of congenital rubella syndrome that developed diabetes mellitus at the age of seven years. The girl had been complaining of diabetes symptoms since six months before admission, but had been misdiagnosed. The patient finally came with symptoms of diabetic ketoacidosis, a life threatening complication of diabetes mellitus. Diabetes mellitus type 1 as a delayed manifestation of congenital rubella syndrome has to be kept in mind to prevent missing the diagnosis.Key words: rubella infection - congenital rubella syndrome - diabetes mellitus type 1ABSTRAKCorina Lisa, Madarina Julia, E.S. Herini - Diabetes Mellitus Tipe 7 pada Sindroma Rubella KongenitalDiabetes melitus adalah salah satu manifestasi lambat sindrom rubella kongenital yang jarang, tetapi perlu diwaspadai. Kami melaporkan satu kasus sindrom rubela kongenital yang mengalami diabetes melitus tipe 1 pad a usia 7 tahun. Meskipun gejala diabetes telah dikeluhkan sejak enam bulan sebelum masuk rumah sakit, penyakit diabetes tetap tidak terdiagnosis. Penderita akhirnya datang dengan gejala dan tanda ketosidosis diabetikum, suatu komplikasi diabetes mellitus yang mengancam jiwa. Manifestasi lambat sindrom rubella yang berupa diabetes mellitus tipe I harus diwaspadai untuk mencegah tidak terdiagnosanya penyakit tersebut.